Apparent diffusion coefficient values of normal testis and variations with age - Athina C Tsili; Dimitrios Giannakis; Anastasios Sylakos; Alexandra Ntorkou; Loukas G Astrakas; Nikolaos Sofikitis; Maria I Argyropoulou (Asian Journal of Andrology, 2014)
The usefulness of diffusion-weighted magnetic resonance imaging (DWI) in the evaluation of scrotal pathology has recently been reported. A standard reference of normal testicular apparent diffusion coefficient (ADC) values and their variations with age is necessary when interpreting normal testicular anatomy and pathology. We evaluated 147 normal testes using DWI, including 71 testes from 53 men aged 20-39 years (group 1), 67 testes from 42 men aged 40-69 years (group 2) and nine testes from six men older than 70 years (group 3). DWI was performed along the axial plane, using a single shot, multislice spin-echo planar diffusion pulse sequence and b-values of 0 and 900 s mm−2 . The mean and standard deviation of the ADC values of normal testicular parenchyma were calculated for each age group separately. Analysis of variance (ANOVA) followed by post hoc analysis (Dunnett T3) was used for statistical purposes. The ADC values (× 10−3 mm 2 s−1 ) of normal testicular tissue were different among age groups (group 1: 1.08 ± 0.13; group 2: 1.15 ± 0.15 and group 3: 1.31 ± 0.22). ANOVA revealed differences in mean ADC among age groups (F = 11.391, P < 0.001). Post hoc analysis showed differences between groups 1 and 2 (P = 0.008) and between groups 1 and 3 (P = 0.043), but not between groups 2 and 3 (P = 0.197). Our findings suggest that ADC values of normal testicular tissue increase with advancing age.